Late Neoproterozoic-to-recent long-term t-T-evolution of the Kaoko and Damara belts in NW Namibia - Krob, Florian C.; Eldracher, Daniel P.; Glasmacher, Ulrich A.; Husch, Sabine; Salomon, Eric; Hackspacher, Peter C. [UNESP]; Titus, Nortin P. (Springer, 2020)
This research aims to reconstruct the Late Neoproterozoic-to-recent long-term time-temperature-evolution of the NW Namibian Kaoko and Damara belts combining numerical modeling of new thermochronological data with previously published geochronological data, i.e., U-Pb, Sm-Nd, and Rb-Sr analyses, and K/Ar, Ar-40/Ar-39 low-temperature thermochronology. Consequently, we retrieve a coherent long-term time-temperature-evolution of the NW Namibian Neoproterozoic basement rocks including rates of exhumation and subsidence periods over the last 500 Myr. Neoproterozoic basement rocks indicate fast post-Pan African/Brasiliano cooling and exhumation, reheating, or rather subsidence during the development of the Paleozoic-to-Mesozoic SW Gondwana intraplate environment and a significant thermal overprint of the rocks during South Atlantic syn- to post-rift processes, and therefore, resemble the opponent SE Brazilian time-temperature-evolution. We provide an overview of thermochronological data including new apatite and zircon fission-track data derived from Neoproterozoic, Late Paleozoic, and Lower Cretaceous rocks. Apatite fission-track ages range from 390.9 +/- 17.9 Ma to 80.8 +/- 6.0 Ma in the NW Kaoko Belt with youngest ages confined to the coastal area and significant age increase towards the inland. New zircon apatite fission-track data reveal ages between 429.5 +/- 47.8 and 313.9 +/- 53.4 Ma for the rocks of the Kaoko Belt. In the central Damara Belt, new apatite fission-track ages range between 138.5 +/- 25.3 Ma to 63.8 +/- 4.8 Ma. Combined apatite fission-track age distributions from Angola to Namibia and SE Brazil correlate for both sides of the South Atlantic passive continental margin and the reset AFT ages overlap with the lateral Parana-Etendeka dike swarm distribution.
Keywords: Long-term t-T-evolution; Thermochronology; Numerical modeling; South Atlantic passive continental margin of NW Namibia